2017
DOI: 10.1111/1471-0307.12328
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of the formulation for barley–milk composite‐based fermented drink

Abstract: The effect of barley flour concentration, Lactobacillus plantarum NCDC344 (Lp344) and co-culture (Streptococcus thermophilus 20) inoculum levels on the sensory quality, Lp344 count, b-glucan content and viscosity of barley-milk composite-based fermented drink was investigated. A central composite rotatable design of response surface methodology was used for optimisation of the formulation. Of the three formulation variables, barley flour concentration was found to be the most critical as it significantly affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Overall acceptability (OA) of AICFMD reflected the panellist's collective choice based on colour, appearance, flavour, consistency and sweetness (Ahuja, 2015). Table 1 indicated that the average OA score of AICFMD ranged from 6.59 to 7.84.…”
Section: Overall Acceptabilitymentioning
confidence: 99%
“…Overall acceptability (OA) of AICFMD reflected the panellist's collective choice based on colour, appearance, flavour, consistency and sweetness (Ahuja, 2015). Table 1 indicated that the average OA score of AICFMD ranged from 6.59 to 7.84.…”
Section: Overall Acceptabilitymentioning
confidence: 99%